Characterization of smallest active monomeric penicillin V acylase from new source: a yeast, rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Prabhune, Asmita; Suresh, C. G.; Pundle, Archana (Process Biochemistry, 2008)
An intracellular monomeric penicillin V acylase (PVA) of 36,000 Da exhibiting pI of 4.19, purified from newly identified yeast source, Rhodotorula aurantiaca (NCIM 3425). The enzyme was purified by hydrophobic interaction chromatography. The enzyme showed optimal activity at 45 degrees C and retained 80% activity after incubation at 45 degrees C and pH 5.5 for I h. The enzyme showed maximum activity at pH 5.5 and was very stable between pH 5.5-6.5 with optimum stability at pH 6.0. It exhibited 50% of its original activity after 30 min incubation at 60 degrees C. Enzyme hydrolyzed substrates with benzyl side chain but preferred penicillin V as primary substrate. N-terminally located serine supports the fact that it belongs to Ntn (N-terminal nucleophile)-hydrolase superfamily. The initial ten amino acid residues of R. aurantiaca PVA were identical to the initial sequence of NADH dehydrogenase (EC 1.6.99.3): however the enzyme lacks dehydrogenase activity. EGTA, EDTA, hexane and ethyl acetate stabilized the activity where as small chain alcohols inhibited it. 1,4-Dioxane, THF (tetrahydrofurane), phenol and benzyl alcohol severely inhibited enzyme activity while BME and DTT increased it. Tween 80 and Tween 20 highly enhanced the activity where as SIDS and Triton X-100 inhibited it. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Intracellular enzyme; N-terminal sequencing; Penicillin V acylase; Purification; Rhodotorula aurantiaca; Substrate specificity